Uncertainty in rainfall input data in a conceptual water balance model: effects on outputs and implications for predictability (2014)
As hydrological models become more prevalent in water resources planning and management, increasing levels of detail and precision are needed. Currently, reliable models that simulate the hydrological behavior of a basin are indispensable; however, it is also necessary to know the limits of the predictability and reliability of the model outputs. The present study evaluates the influence of uncertainty in the main input variable of the model, rainfall, on the output uncertainty of a hydrological model. Using concepts of identifiability and sensitivity, the uncertainty in the model structure and parameters was estimated. Then, the output uncertainty caused by uncertainties in i) the rainfall amounts and ii) the periods of the rainfall was determined. The main conclusion is that uncertainty in rainfall estimation during rainy periods produces greater output uncertainty. However, in non-rainy periods, the output uncertainty is not very sensitive to the uncertainty in rainfall. Finally, uncertainties in rainfall during the basin filling and emptying periods (Apr. – Jun. and Sep. – Nov., respectively) alter the uncertainty in subsequent periods. Therefore, uncertainties in these periods could result in limited ranges of model predictability. ResumenLos modelos hidrológicos se han vuelto cada vez más necesarios en la planificación y gestión de recursos hídricos, donde un aumento en los niveles de detalle y precisión es necesario. Actualmente disponer de modelos para simular el comportamiento hidrológico de una cuenca resulta indispensable, sin embargo, también es necesario conocer los límites de predictibilidad y de confiabilidad de las salidas de un modelo. En este estudio se evalúan la influencia de la incertidumbre en la principal entrada de un modelo, la precipitación, sobre la incertidumbre de las salidas de un modelo hidrológico. Utilizando conceptos de identificabilidad y sensibilidad se estima la incertidumbre de los parámetros y estructura de un modelo. Luego, la incertidumbre en las salidas causadas por incertidumbre en i) los montos de precipitación, ii) los períodos de precipitación fue calculada. Como conclusiones se obtuvo que la incertidumbre en la estimación de la precipitación en períodos de lluvia produce mayor incertidumbre sobre las salidas. En períodos no lluviosos, la incertidumbre de las salidas es poco sensible a incertidumbre sobre las precipitaciones. Finalmente, incertidumbres en periodos de llenado y vaciado (Abril-Junio y Septiembre-Noviembre respectivamente) afectan la incertidumbre en las salidas en los períodos subsecuentes. Por lo tanto incertidumbres en aquellos períodos pueden resultar en rangos limitados de predictibilidad de un modelo.